2(5x + 6) + 2 =-6x+ Box x+ Box

1 answer

Expanding the expression on the left side of the equation:

2(5x + 6) + 2 = 10x + 12 + 2 = 10x + 14

So the equation becomes:

10x + 14 = -6x + Box x + Box

Now, let's gather the like terms:

10x + 6x = -14 + Box x + Box

Combining like terms:

16x = -14 + Box x + Box

To solve for x, we need to isolate the variable x. Subtracting the terms which do not contain x from both sides of the equation:

16x - Box x = -14 + Box

Simplifying:

15x = -14 + Box

So the equation is:

15x = -14 + Box